Nanocomposite based on SiC/Si: a new biomorphic material for maxillofacial surgery (experimental studies) - Kartel, M.; Zhukovtseva, O.; Malanchuk, V.; Kiselov, V.; Aleksyeyeva, T.; Bo, Wang (Поверхность, 2015)
The aim of the study was to investigate the interaction of experiment samples biomorphic ceramics based on silicon carbide with bone tissue by scanning electron microscopy. To achieve this goal in a laboratory experiment 20 rats underwent implantation of test material samples in the lower jaw bone tissue. Animals were removed from the experiment in terms of 7, 30 and 90 days after the start of the experiment and the subsequent investigation of the material surface and area of it contact with the bone tissue.